2004
DOI: 10.1007/s10384-003-0022-2
|View full text |Cite
|
Sign up to set email alerts
|

Gelatinase Expression in Ocular Surface Disorders

Abstract: MMP-2, MMP-9, and MT1-MMP, which activates MMP-2, were expressed in the patients with various ocular surface disorders. In ocular surface disorders, therefore, the expression of gelatinases is upgraded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…[78][79][80][81] Because the high-airflow, low-humidity controlled environments that we all live and work in are an …”
Section: Combined Alkali Burn and Dry Eyementioning
confidence: 99%
“…[78][79][80][81] Because the high-airflow, low-humidity controlled environments that we all live and work in are an …”
Section: Combined Alkali Burn and Dry Eyementioning
confidence: 99%
“…For clinicians, two potentially separate aspects of ocular surface disease are of primary concern, first, making the diagnosis of ocular surface disease, 5 and second, determining the optimal therapy and monitoring its efficacy. It is usually referred to as dysfunctional tear syndrome (DTS), dry eye, and keratitis sicca.…”
Section: Keratitis Siccamentioning
confidence: 99%
“…Few studies have reported the expression of MMPs in healthy and diseased corneas. MMP‐2 and MMP‐9 have been identified by immunohistochemistry in healthy and ulcerated corneas in humans, 22,33,34 dogs 21,35 (Fig. 2), mice, 36 rats, 37,38 and horses 39 (Fig.…”
Section: Immunolocalization Of Mmp‐2 and Mmp‐9 In Healthy And Diseasementioning
confidence: 99%